Soluble magnesium alloy material and soluble bridge plug using soluble magnesium alloy

By using soluble bridge plugs made of new soluble magnesium alloy materials, the problem that the existing technology cannot meet the fracturing construction requirements in high temperature, high pressure and complex liquid environments is solved, effective sealing and rapid dissolution under different conditions are achieved, and normal production after fracturing is ensured.

CN119710400APending Publication Date: 2025-03-28CHINA PETROCHEMICAL CORP +3

Patent Information

Application Number
CN202311251448.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-26
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Existing soluble bridge plugs cannot meet the multiple requirements of fracturing construction in high temperature, high pressure and complex liquid environments, including well entry, pumping, seating, sealing and rapid dissolution.

Method used

A new soluble magnesium alloy material, including magnesium, zinc, aluminum, nickel, copper and other elements, is used to make a soluble bridge plug made by adjusting the mass percentage and combination of each element. The dissolution rate of each component is adjustable to adapt to the environment of different temperatures and chloride concentrations.

Benefits of technology

It realizes effective sealing and rapid dissolution of soluble bridge plugs under different construction conditions, meets the requirements of 70MPa high-pressure working pressure difference, 24-hour effective sealing time and rapid dissolution within 15 days, and ensures normal liquid discharge and production channels after fracturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710400A_ABST
    Figure CN119710400A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of oil and gas downhole tools, and particularly relates to a soluble magnesium alloy material and a soluble bridge plug using soluble magnesium alloy. The soluble magnesium alloy material comprises the following components in percentage by mass: magnesium gt, zinc gt, aluminum gt, nickel gt and copper gt. The alloy comprises 85% of zinc, 2-5% of zinc, 2-4% of aluminum, 1-3% of nickel and 1- The problem that an existing material cannot be suitable for the current stratum environment can be solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of oil and gas downhole tools, and in particular, relates to a soluble magnesium alloy material and a soluble bridge plug using the soluble magnesium alloy. Background Art

[0002] At present, in the process of oil and gas well operation, soluble bridge plugs have been widely used for formation isolation. The use of bridge plugs for formation isolation can effectively achieve staged fracturing.

[0003] As the drilling depth of oil and gas wells increases, the wellbore temperature and pressure become higher and higher, the wellbore liquid medium becomes more and more complex, and the requirements for soluble bridge plugs become higher and higher.

[0004] At present, the operating environment parameters of soluble bridge plugs include: wellbore temperature: ① ultra-low temperature of 30-50℃, ② low temperature of 50-80℃, ③ medium temperature of 80-120℃, ④ high temperature of 120-150℃, ⑤ ultra-high temperature of 150-200℃; construction liquid environment: ① low chloride concentration of 0-5000mg / l, ② medium chloride concentration of 5000-10000mg / l, ③ high chloride concentration of 1000-30000mg / l, ④ medium environment with ultra-high chloride concentration greater than 30000mg / l.

[0005] The fracturing construction requirements of soluble bridge plugs include: achieving the entry, pumping, setting and releasing of soluble bridge plugs under different construction conditions, 70MPa high-pressure working pressure difference, 24 hours of effective sealing time and rapid dissolution within 15 days, while not affecting the normal rapid dissolution of the soluble bridge plug after fracturing, ensuring the normal channel for drainage and production after fracturing.

[0006] The current soluble bridge plugs cannot meet all of the above construction requirements and use environments due to material limitations.

[0007] Chinese patent document CN111531179A discloses a magnesium alloy for an anti-erosion and easily decomposable fracturing bridge plug system and a preparation method thereof. The preparation method of the magnesium alloy comprises the following steps: (1) selecting a magnesium alloy raw material and processing it into powder or crumb particles; (2) subjecting the processed magnesium alloy raw material to secondary ball milling, and adding Si, Cu, Fe, Al, Zn, SiO 2and one or more of SiC, to obtain magnesium alloy chips with a particle difference within 5% to 30% and a total mesh number between 12 and 100; (3) placing the magnesium alloy chips in a sleeve for rotary centrifugal treatment, combined with vibration; (4) cold isostatic pressing the treated billet; (5) heating the billet after cold isostatic pressing, and evacuating it again, while hot isostatic pressing; (6) taking out the billet and directly extruding it on an extruder to obtain a magnesium alloy rod. The bridge plug prepared by the magnesium alloy can be used in the exploration process of oil and gas fields with impact environment and large amount of sediment environment. The patent discloses the magnesium alloy used in the bridge plug and the preparation method, but does not mention the specific amount of various components of the magnesium alloy and the dissolution rate.

[0008] Chinese patent document CN104651691B discloses a fast-degrading magnesium alloy material and its manufacturing method and application. A fast-degrading magnesium alloy material, including the following components Al, Li, Ca, Y, Si, Ni, Cu, Fe and other elements, also discloses the preparation method and application of the fast-degrading magnesium alloy material. Although the patent mentions fast-degrading magnesium alloy materials with high temperature resistance of 130°C or even 170°C and its manufacturing method and application, it does not subdivide the dissolution rate of bridge plugs under different temperatures and mineralization environments to form a sequence of fully soluble bridge plugs with different temperatures and dissolution rates. The description is relatively general, the user selectivity is small, the cost is difficult to control, and the bridge plug involved in the present invention has a temperature resistance index of 200°C to cope with high temperature characteristics. Summary of the invention

[0009] In view of the above-mentioned technical problems, the present invention aims to provide a soluble magnesium alloy material, which can be suitable for the use environment of the above-mentioned background technology under the premise of meeting the requirements of fracturing construction.

[0010] The present invention also provides a soluble bridge plug, which is made of the soluble magnesium alloy provided by the present invention.

[0011] According to the present invention, a soluble magnesium alloy material is provided, comprising magnesium, zinc, aluminum, nickel and copper, wherein the mass percentage of each component is: magnesium>85%, zinc 2-5%, aluminum 2-4%, nickel 1-3% and copper 1-3%.

[0012] In a preferred embodiment, the soluble magnesium alloy material further includes neodymium and / or cerium.

[0013] In a preferred embodiment, the mass percentage of neodymium is 0-2%.

[0014] In a preferred embodiment, the mass percentage of cerium is 0-2%.

[0015] According to the present invention, there is also provided a soluble bridge plug, comprising a central tube, a cone, a slip and a guide shoe, wherein at least some parts of the soluble bridge plug are made of the soluble magnesium alloy material provided by the present invention.

[0016] In a preferred embodiment, the central tube, the cone, the slips and the guide shoes are made of the soluble magnesium alloy material provided by the present invention.

[0017] In a preferred embodiment, the dissolution rates of the central tube, the cone, the slips and the guide shoes are not completely equal.

[0018] In a preferred embodiment, the dissolution rate of the center tube and the slips is slower than the dissolution rate of the cone.

[0019] In a preferred embodiment, the dissolution rate of the guide shoe is faster than the dissolution rate of the cone.

[0020] In a preferred embodiment, the dissolution rate of the central tube, the cone, the slips and the guide shoes is 0.11-0.51 g·m -2 ·h -2 .

[0021] Compared with the prior art, the advantages of the present application are as follows.

[0022] The soluble magnesium alloy material of the present invention can realize the requirements of fracturing construction under different construction conditions. The soluble bridge plug of the present invention is made of soluble magnesium alloy material. The various components of the soluble bridge plug adopt elemental components of different components and different proportions of components to adapt to the construction environment and dissolution requirements of different temperatures and different chloride concentrations. The soluble magnesium alloy material is mainly composed of elemental magnesium Mg (>85%, mass percentage, the same below), and also includes zinc Zn (2-5%), aluminum Al (2-4%), nickel Ni (2-3%), copper Cu (2-3%) and other common non-ferrous metal elements. In addition, it also includes neodymium Nd (0-2%), cerium Ce (0-2%) and other rare metal elements, thereby forming a corrosion rate of 0.31g·m -2 ·h -2 The fluctuation range of the dissolution rate was controlled within the range of 0.11 to 0.51 g·m -2 ·h -2 , in order to realize the entry, pumping, sealing and releasing of the soluble bridge plug under different construction conditions, 70MPa high-pressure working pressure difference, 24 hours of effective sealing time, and rapid dissolution within 15 days, that is, to meet the fracturing construction requirements of the soluble bridge plug, while not affecting the normal and rapid dissolution of the soluble bridge plug after the fracturing, ensuring the normal channel for drainage and production after fracturing. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The present invention will be described below with reference to the accompanying drawings.

[0024] Figure 1 A schematic diagram showing an embodiment of a soluble bridge plug according to the present invention is shown.

[0025] In the figure:

[0026] 1. Center tube; 2. Rubber cylinder; 3. Metal support ring; 4. Cone; 5. Slip; 6. Guide shoe; 7. Anchoring tooth; 8. Lower rubber cylinder protection ring; 9. Threaded connection sleeve; 10. Floating rubber cylinder shoulder ring; 12. Large diameter part; 13. Small diameter part; 100. Soluble bridge plug.

[0027] In the present application, all drawings are schematic drawings, which are only used to illustrate the principles of the present invention and are not drawn according to the actual scale. DETAILED DESCRIPTION

[0028] Embodiment 1:

[0029] In one embodiment of the present invention, a soluble magnesium alloy material is provided, including magnesium, zinc, aluminum, nickel and copper, and the mass percentage of each component is: magnesium>85%, zinc 2-5%, aluminum 2-4%, nickel 1-3%, and copper 1-3%.

[0030] Under the composition combination of the present invention, the effect of the element zinc Zn is mainly to improve the performance of the surface film, while increasing the allowable concentrations of the element nickel Ni and the element copper Cu in the soluble magnesium alloy material.

[0031] Under this component combination of the present invention, as the content of elemental aluminum Al gradually increases, the corrosion rate of the soluble magnesium alloy material decreases significantly. When the content of elemental aluminum Al reaches 4% and further increases, the effect of reducing the corrosion rate will gradually slow down.

[0032] In this combination of components of the present invention, the elements nickel Ni and copper Cu are the elements that accelerate the corrosion rate in magnesium alloys. They have a small solid solubility in soluble magnesium alloy materials, are easy to precipitate, and have a small hydrogen evolution overpotential. When corrosion occurs, they act as cathodes to accelerate the cathode reaction in the corrosion process, thereby accelerating the corrosion rate.

[0033] Furthermore, in a preferred embodiment, the soluble magnesium alloy material also includes neodymium and / or cerium.

[0034] Specifically, the mass percentage of neodymium is 0-2%, and the mass percentage of cerium is 0-2%.

[0035] Under this composition combination of the present invention, the main function of the element neodymium Nd in the soluble magnesium alloy material is to improve the strength and corrosion resistance of the soluble magnesium alloy material, making them more durable and reliable. The hardness of the soluble magnesium alloy material increases with the increase of the content of the element neodymium Nd, and the room temperature tensile strength of the soluble magnesium alloy material can also be increased. When the content of the element neodymium Nd exceeds 3.0%, the room temperature tensile strength of the soluble magnesium alloy material tends to decrease. Therefore, in this embodiment, the content of the element neodymium Nd (0-2%) is controlled to adjust the overall compressive strength and corrosion resistance of the soluble magnesium alloy material.

[0036] Under this composition combination of the present invention, the role of the element Ce is to form fine equiaxed crystals, thereby effectively improving the casting structure and microstructure of the soluble magnesium alloy material. By setting the element Ce, the grain boundary of the soluble magnesium alloy material can be strengthened during high temperature deformation. Adding an appropriate amount of Ce (content 0-2%) to the soluble magnesium alloy material can improve the tensile strength, yield strength and elongation of the soluble magnesium alloy material.

[0037] Under this setting of the present embodiment, the reference value of the dissolution rate of the soluble magnesium alloy material can be set at 0.31 g·m -2 ·h -2 By adjusting each component within the value range of the above components, the dissolution rate of the soluble magnesium alloy material is adjusted to 0.11-0.51 g·m -2 ·h -2 .

[0038] Embodiment 2:

[0039] In another embodiment of the present invention, a soluble bridge plug 100 is provided, comprising a central pipe 1, a cone 4, a slip 5 and a guide shoe 6. The specific structure of the soluble bridge plug 100 is described in detail in Embodiment 6.

[0040] At least part of the components of the soluble bridge plug 100 are made of the soluble magnesium alloy material provided by the present invention.

[0041] It should be noted that, although Example 6 of the present invention discloses a structure of a soluble bridge plug 100, the soluble bridge plug 100 of the present invention is not limited to this structure. As long as at least one part of the soluble bridge plug 100 is made of the soluble magnesium alloy material provided by the present invention, it should be within the protection scope of the present invention.

[0042] In this embodiment, the central tube 1, the cone 4, the slips 5 and the guide shoes 6 are made of the soluble magnesium alloy material provided by the present invention.

[0043] In a preferred embodiment, the dissolution rates of the central pipe 1, the cone 4, the slips 5 and the guide shoes 6 are not completely equal. That is, the dissolution rates of the various parts of the soluble bridge plug 100 may be equal or different. The dissolution rates of the various parts of the soluble bridge plug 100 in this embodiment are different, so that it can better adapt to various different working conditions.

[0044] Specifically, by adjusting the value range of each component of the soluble magnesium alloy material in the first embodiment, the dissolution rate of the central tube 1, the cone 4, the slip 5 and the guide shoe 6 can be adjusted, so that the central tube 1, the cone 4, the slip 5 and the guide shoe 6 have different dissolution rates. In other words, according to different working conditions, the soluble magnesium alloy material of each part of the soluble bridge plug 100 adopts elemental components of different components and different proportions of components to adapt to different temperatures, construction environments with different chloride concentrations and dissolution requirements.

[0045] In a preferred embodiment, the dissolution rate of the main pressure-bearing components of the soluble bridge plug 100 is slower than the dissolution rate of the cone. Specifically, in this embodiment, the dissolution rate of the main pressure-bearing components of the soluble bridge plug 100, such as the central pipe 1 and the slips 5, is slower than the dissolution rate of the cone 4.

[0046] In a preferred embodiment, the auxiliary parts of the soluble bridge plug 100 have the fastest dissolution rate. Specifically, in this embodiment, the dissolution rate of the auxiliary parts such as the guide shoe 6 of the soluble bridge plug 100 is faster than that of the cone 4, the central pipe 1 and the slip 5.

[0047] In a preferred embodiment, the dissolution rate of the central tube 1, cone 4, slip 5 and guide shoe 6 is 0.11-0.51 g·m -2 ·h -2 .

[0048] Embodiment three:

[0049] The target formation temperature of a coalbed methane vertical and inclined well in a certain area is 30-50℃ (ultra-low temperature), the construction water is clean water (chloride concentration ≤5000mg / L), and the construction does not require acid treatment or CO 2Note: the main components of the formula of the soluble magnesium alloy material used to make the soluble bridge plug 100 parts (mass percentage content > 99.5%, that is, the mass percentage content of magnesium, zinc, aluminum, nickel, copper, neodymium, and cerium is greater than 99.5% of the overall soluble magnesium alloy material, and the rest can be understood as impurities): magnesium Mg accounts for 91.0%, zinc Zn accounts for 2.9%, aluminum Al accounts for 2.2%, nickel Ni accounts for 1.2%, copper Cu accounts for 2.0%, neodymium Nd accounts for 0.25%, and cerium Ce accounts for 0.12%. Combined with the structure of the soluble bridge plug 100 of the present invention, it can meet 70MPa high-pressure working pressure difference, 24 hours of effective sealing time, and rapid dissolution within 15 days.

[0050] Embodiment 4:

[0051] The target formation temperature of a tight volcanic oil and gas horizontal well in a certain area is 80-120℃ (medium temperature), the construction water is clean water (5000mg / L≤chloride concentration≤10000mg / L), and no acid treatment or CO is required for construction. 2 Note: the main components of the soluble bridge plug formula (content > 99.5%, that is, the mass percentage of magnesium, zinc, aluminum, nickel, copper, neodymium and cerium in the overall soluble magnesium alloy material is greater than 99.5%, and the rest can be understood as impurities): magnesium Mg accounts for 89.0%, zinc Zn accounts for 2.5%, aluminum Al accounts for 2.4%, nickel Ni accounts for 1.3%, copper Cu accounts for 2.5%, neodymium Nd accounts for 1.2%, and cerium Ce accounts for 0.85%. Combined with the structure of the soluble bridge plug 100 of the present invention, it can meet 70MPa high-pressure working pressure difference, 24 hours of effective sealing time, and rapid dissolution within 15 days.

[0052] Embodiment five:

[0053] The target formation temperature of a tight oil horizontal well in a certain block is 150-200℃ (ultra-high temperature), and the construction water is high-chlorine backflow fluid (chloride concentration ≥30000mg / L). During the construction process, acid pretreatment or CO injection is required. 2 The main components of the soluble bridge plug formula (content > 99.5%, that is, the mass percentage of magnesium, zinc, aluminum, nickel, copper, neodymium, and cerium in the overall soluble magnesium alloy material is greater than 99.5%, and the rest can be understood as impurities): magnesium Mg accounts for 86%, Zn accounts for 2.9%, aluminum Al accounts for 2.8%, nickel Ni accounts for 1.22%, copper Cu accounts for 2.85%, neodymium Nd accounts for 1.87%, and cerium Ce accounts for 2%. Combined with the structure of the soluble bridge plug 100 of the present invention, it can meet 70MPa high-pressure working pressure difference, 24 hours of effective sealing time, and rapid dissolution within 15 days.

[0054] Embodiment six:

[0055] In one embodiment of the present invention, a soluble bridge plug 100 is provided, such as Figure 1 It should be noted that the directional terms or qualifiers "left", "right", etc. used in this application are all directed to the referenced Figure 1 They are not intended to define the absolute positions of the components involved, but may vary depending on the circumstances.

[0056] like Figure 1 As shown, the soluble bridge plug 100 comprises a central pipe 1 , a cone 4 , a slip 5 and a guide shoe 6 which are coaxially arranged in sequence, and a rubber sleeve 2 is arranged outside the central pipe 1 .

[0057] The center pipe 1 is connected to the cone 4 through threads, the slip 5 is connected to the cone 4 through a conical surface, and the slip 5 is connected to the guide shoe 6 through threads.

[0058] In a preferred implementation, a soluble corrosion-inhibiting particle coating (tungsten carbide coating) is provided on the inner and outer surfaces of the central tube 1, the cone 4, the slip 5 and the guide shoe 6. The acid-proof performance of the soluble bridge plug 100 can be improved by spraying the soluble corrosion-inhibiting particle coating mainly containing tungsten carbide. Among them, the content of tungsten carbide in the material mainly containing tungsten carbide is more than 95%.

[0059] In a preferred embodiment, a resin shatterable protective film is provided on the slip 5. It is easy to understand that the specific composition of the resin shatterable protective film is prior art and is not the technical point of the present invention, and will not be repeated here. The resin shatterable protective film can prevent the slip 5 from directly contacting the well fluid. The resin shatterable protective film can protect the slip 5 from reacting with the well fluid within 24 hours. After 24 hours, the resin shatterable protective film falls off, and the slip 5 reacts quickly with the well fluid.

[0060] The soluble bridge plug 100 can perform sealing operations under high temperature, high pressure and acidic environment, and can dissolve after a certain period of time, thereby improving work efficiency.

[0061] A plurality of anchor teeth 7 are provided on the outer wall of the slip 5. In a preferred embodiment, as Figure 1 As shown, at least four circles of anchor teeth 7 are arranged on the outer wall of the slip 5, and the anchor teeth 7 are made of high-strength ceramic particles.

[0062] In a preferred embodiment, the slips 5 and the anchor teeth 7 are made of high-strength ceramic particles of 8×5 mm or 9.5×7.5 mm. After the slips 5 are dissolved, the insoluble matter remaining in the well is less than 2%, thereby facilitating the dissolution of the bridge plug.

[0063] In this embodiment, the central pipe 1 and the guide shoe 6 are made of 7050 aluminum alloy. Under this configuration, the soluble bridge plug 100 can withstand a pressure of 70 MPa and a temperature range of 150°C to 200°C, and can withstand pressure, dissolve quickly, and completely dissolve within 6 to 10 days after construction in a complex wellbore environment.

[0064] In a preferred embodiment, the thickness of the tungsten carbide coating is set to 0.5-1.0 mm. The tungsten carbide coating prevents the central tube 1, cone 4, slip 5 and guide shoe 6 from reacting with 15% hydrochloric acid within 8 hours, delays the reaction time of 7050 aluminum alloy with hydrochloric acid, improves sealing efficiency, and enables the bridge plug to achieve ultra-high temperature resistance and acid corrosion resistance.

[0065] In a preferred embodiment, an external thread is provided on the outer wall of the central tube 1 , and the cone 4 is connected to the external thread of the central tube 1 .

[0066] like Figure 1 As shown, the center tube 1 includes a large diameter portion 12 and a small diameter portion 13 , a threaded connection sleeve 9 is threadedly provided on the right outer wall of the small diameter portion 13 of the center tube 1 , and the cone 4 is threadedly connected to the center tube 1 via the threaded connection sleeve 9 .

[0067] In a preferred embodiment, the outer walls of both axial ends of the rubber cylinder 2 are tapered. One end of the rubber cylinder 2 extends into the large diameter portion 12 , and the axial end surface and radial outer wall of the rubber cylinder 2 abut against the large diameter portion 12 .

[0068] A metal support ring 3 is provided on the center tube 1, and the metal support ring 3 is provided at one end of the principal large diameter portion 12 of the rubber cylinder 2. The shape of the metal support ring 3 is adapted to the shape of the rubber cylinder 2, so that the axial end face and the radial outer wall of the rubber cylinder 2 are both in contact with the metal support ring 3. A lower rubber cylinder protection ring 8 is provided between the metal support ring 3 and the rubber cylinder 2, and the shape of the lower rubber cylinder protection ring 8 is also adapted to the contact surface between the metal support ring 3 and the rubber cylinder 2.

[0069] In a preferred embodiment, a floating rubber sleeve shoulder ring 10 is provided at one end of the rubber sleeve 2 away from the metal support ring 3, that is, at the end close to the large diameter portion 12. The axial left end of the floating rubber sleeve shoulder ring 10 abuts against the large diameter portion, and the inner wall of the floating rubber sleeve shoulder ring 10 is set to a shape that matches the cone at the end of the rubber sleeve 2.

[0070] The soluble bridge plug 100 can perform seating, isolation, and sealing pressure-bearing operations in an acidic environment with an ultra-high temperature formation temperature of more than 150°C, a high-pressure working pressure difference of 70MPa, and a hydrochloric acid concentration of 10% or less, thereby providing a safe and efficient interlayer isolation guarantee for ultra-high temperature and dense layers that require ultra-high temperature, high pressure, and acid treatment of the formation, improving the working efficiency of the ultra-high temperature and acid-resistant soluble bridge plug, while not affecting the normal dissolution of the soluble bridge plug after the fracturing is completed, ensuring the normal channel for drainage and production after fracturing.

[0071] In a preferred embodiment, except for the rubber cylinder 2, the remaining parts of the soluble bridge plug 100 can be made of the soluble magnesium alloy material in the first embodiment of the present invention. The specific parts made of the soluble magnesium alloy can be determined according to the actual working conditions.

[0072] In the description of the present invention, it should be understood that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0073] In the present invention, unless otherwise clearly specified and limited, the terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be an indirect connection through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0074] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0075] Finally, it should be noted that the above is only a preferred embodiment of the present invention and does not constitute any limitation to the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for a person skilled in the art to modify the technical solutions described in the aforementioned embodiments or to replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A soluble magnesium alloy material, characterized in that: It includes magnesium, zinc, aluminum, nickel and copper, and the mass percentage of each component is: magnesium>85%, zinc 2-5%, aluminum 2-4%, nickel 1-3%, and copper 1-3%.

2. The soluble magnesium alloy material according to claim 1, characterized in that: The soluble magnesium alloy material further comprises neodymium and / or cerium.

3. The soluble magnesium alloy material according to claim 2, characterized in that: The mass percentage of neodymium is 0 to 2%.

4. The soluble magnesium alloy material according to claim 2, characterized in that: The mass percentage of cerium is 0 to 2%.

5. A soluble bridge plug, comprising a central tube, a cone, a slip and a guide shoe, characterized in that: At least some parts of the soluble bridge plug are made of the soluble magnesium alloy material according to any one of claims 1 to 4.

6. The soluble bridge plug according to claim 5, characterized in that: The central tube, the cone, the slips and the guide shoes are made of the soluble magnesium alloy material according to any one of claims 1 to 4.

7. The soluble bridge plug according to claim 6, characterized in that: The dissolution rates of the central tube, the cone, the slips and the guide shoes are not completely equal.

8. The soluble bridge plug according to claim 7, characterized in that: The dissolution rate of the center tube and the slips is slower than the dissolution rate of the cone.

9. The soluble bridge plug according to claim 8, characterized in that: The dissolution rate of the guide shoe is faster than the dissolution rate of the cone.

10. The soluble bridge plug according to claim 6, characterized in that: The dissolution rate of the central tube, the cone, the slips and the guide shoes is 0.11 to 0.51 g·m -2 ·h -2 .

Citation Information

Patent Citations

  • Rapidly degradable magnesium alloy materials, their manufacturing methods and applications

    CN104651691B

  • Magnesium alloy for anti-scouring easily-decomposable fracturing bridge plug system and preparation and machining method thereof

    CN111531179A

Cited By

  • Seawater-based high-salinity ultrahigh-temperature high-pressure-difference fully-soluble bridge plug

    CN122106472A

  • Soluble magnesium alloy for oil pipeline bridge plug and method for producing the same

    CN122791235A